Strengthening Solidarity to Enhance the Role of New University Students in Community Engagement - Saputra, Harius Eko; Yusuarsono, Yusuarsono; Yanto, Yanto; Imanda, Antonio (UKInstitute, 2021)
This article discusses the importance of the role of new university students in community engagement and how solidarity can be strengthened to support their social character development. New students often face difficulties in adjusting to the university environment, which can lead to social alienation and a lack of understanding of their roles as agents of change. Through a designed community service program, known as